Nilai-nilai humanisme dalam dialog antar agama perspektif Gus Dur - S. Ag, Muhammad Aqil (Kopertais Wilayah X Jawa Tengah, 2019)
AbstractThe figure of Gus Dur is a unique figure and his thoughts are typical. For most people, his thoughts are difficult to guess and difficult to digest by ordinary lay people, making him a controversial figure as well as being admired. Gus Dur as a teacher of the nation and an intellectual figure is a person who upholds the values of humanism. His struggle in upholding human rights made him highly respected by people from various backgrounds and different identity backgrounds. In particular his defense of the rights of oppressed minorities from both religion and ethnicity. Solving problems during conflicts by promoting dialogue that upholds human values makes Abdurrahman a reliable mediator. His thinking about humanism, is ideally implemented in interfaith dialogue, he offers a concept that is more focused on the human side, human rights themselves rather than dialogue that is theological in nature. ,